The cat who saved books - Natsukawa, Sōsuke, 1978- (Picador ; Thomson press, 2022)
"Bookish high school student Rintaro Natsuki is about to close the secondhand bookstore he has inherited from his beloved bookworm grandfather. However, one day, a talking cat named Tiger appears and asks Rintaro to save books with him. Of course, "ask" is putting it politely -- Tiger is demanding Rintaro's help. The world is full of lonely books, left unread and unloved, and only Tiger and Rintaro can liberate them from their neglectful owners. And so, the odd couple begin an amazing journey, entering different mazes to set books free. Through their travels, Tiger and Rintaro meet a man who leaves his books to rot on his bookshelf, a book torturer who cuts books to clips to help people read as fast as they can, and a publishing drone who only wants to create bestsellers. And then, the last maze that awaits leads Rintaro down a realm only the bravest readers would dare enter... Books, cats, first love, fantasy -- THE CAT WHO SAVED BOOKS is a story for those who know books are so much more than words on paper."--